Surface ablation of 52100 bearing steel using femtosecond laser irradiation - Maharjan, Niroj (2018)
Laser ablation is a rapid-material removal technique with potential application in remanufacturing of bearings to clean damaged surfaces. This study reports the ablation morphology and change in surface composition of 52100 bearing steel irradiated with a femtosecond laser. A smooth ablated surface was achieved by operating the laser at fluence just above the ablation threshold, but higher fluences resulted in roughened surfaces with recast formation. Such coarse morphology is believed to result from higher energy deposition and surface melting. Minimal oxidation occurred at lower fluences. Periodic ripple patterns formed in the ablated area at low fluence; their morphology and possible formation mechanism is discussed.